The role of carbon pricing policy on environment, social, and governance performance in Asia countries / Inten Meutia ... [et al.] - Meutiaa, Inten; F Kartasari, Shelly; Yusrianti, Hasni; Daud, Rochmawati (UiTM Press, 2024)
This study analyses the relationship between countries’ regulatory context and Environment, Social, and Governance (ESG) Performance. Little attention has been paid to how carbon pricing policy influences companies’ ESG performance. This study used data from 2,600 companies from 11 countries in Asia, both with and without carbon policies, to test whether there was a difference in ESG scores between the two groups of countries. This study found that the ESG score in countries with carbon pricing policies was lower than the ESG in countries without carbon pricing policies. This difference proved to be significant. In the context of this research, the Environment Modernization Theory has not been proven to be able to encourage corporate reporting activities and improve corporate ESG performance. This was the first research considering carbon pricing policy regulations in the study of ESG, especially in Asia.